1992
DOI: 10.1111/j.1471-0528.1992.tb13728.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal scalp and umbilical artery blood lactate measured with a new test strip method

Abstract: Objective To compare the measurement of lactate in fetal scalp and umbilical artery blood by a new dry reagent strip method with a commercially available enzymatic method using plasma (Monotest). Design Comparative study. Subjects Fetal scalp blood samples were obtained during labour from 24 fetuses and umbilical artery blood samples were obtained at birth in a further 51 deliveries. Results The concentration of lactate in scalp and umbilical artery blood measured by the reagent strip m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…It is a known fact that reflectometric methods, where plasma diffusion through a filter is included in the analyzing technique, can give false low readings due to slower dif-fusion of the plasma in samples with high Hkt [5,8]. With the electrochemical device lower measurements with high Hkt has been reported previously, especially for specimen with high lactate concentrations [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a known fact that reflectometric methods, where plasma diffusion through a filter is included in the analyzing technique, can give false low readings due to slower dif-fusion of the plasma in samples with high Hkt [5,8]. With the electrochemical device lower measurements with high Hkt has been reported previously, especially for specimen with high lactate concentrations [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, earlier lactate determinations have only been carried out in research projects as sampling volumes needed were large, a minimum of 150 , thereby making it not practical in the analysis in fetal scalp blood samples (FBS) in the clinical management of intrapartum fetal distress. With the launch of new microvolume test strip methods (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) renewed interest for lactate determinations in obstetric practice has emerged [5,7]. Today at least two test strip lactate meters are available on the market, the Accusport™ (Boeringer Mannheim, East Sussex, UK) and the Lactate Pro™ (KDK Corporation, Kyoto, Japan) (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The test range is 0.7-26 mmol/1 for plasma samples. The method has been reported to be accurate and reliable [13]. The enzymat ic reaction requires lactate oxidase and fcrrocyanide as an electron mediator.…”
Section: Blood Glucose and Lactate Measurementmentioning
confidence: 99%
“…However, there is dissatisfaction with the use of umbilical cord acid base measurements as it may not be a good predictor of hypoxic encephalopathy or long-term sequelae associated with birth asphyxia. Animal studies have demonstrated the potential value of lactate measurements and studies are in progress to clarify its clinical usefulness as part of a 'biochemical Apgar score' [22,24]. Our study shows that Accusport is a convenient, easy to use system which provides accurate assessment of cord arterial lactate levels in the newborn and can possibly be used reliably to measure lactate from fetal scalp blood.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies have shown that fetal scalp blood lactate may also be used to accurately predict a depressed fetus [11,22]. Scalp pH reflects a transient respiratory acidosis which may be due to transient hypercapnia, a common event during normal labour [23].…”
Section: Discussionmentioning
confidence: 99%